Brain vital sign monitoring of sleep deprivation detects situational cognitive impairment - Jones, Katherine B.; Frizzell, Tory; Fickling, Shaun; Pawlowski, Gabriela; Brodie, Sonia M.; Lakhani, Bimal; Venter, Jan; D’Arcy, Ryan C. N. (Frontiers in Human Neuroscience, 2024)
Objective, rapid evaluation of cognitive function is critical for identifying situational impairment due to sleep deprivation. The present study used brain vital sign monitoring to evaluate acute changes in cognitive function for healthy adults. Thirty (30) participants were scanned using portable electroencephalography before and after either a night of regular sleep or a night of total sleep deprivation. Brain vital signs were extracted from three established event-related potential components: 1) the N100 (Auditory sensation); 2) the P300 (Basic attention); and 3) the N400 (Cognitive processing) for all time points. As predicted, the P300 amplitude was significantly reduced in the sleep deprivation group. The findings indicate that it is possible to detect situational cognitive impairment due to sleep deprivation using objective, rapid brain vital sign monitoring.